Innovations in practice: piloting electronic session-by-session monitoring in child and adolescent mental health : a preliminary study - Hall, Charlotte L.; Moldavsky, Maria; Taylor, John A.; Marriott, Michael; Goodman, Robert; Sayal, Kapil; Hollis, Chris (Wiley, 2015)
Background